-2(45-5)-10=-3

Simple and best practice solution for -2(45-5)-10=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(45-5)-10=-3 equation:


Simplifying
-2(45 + -5) + -10 = -3

Combine like terms: 45 + -5 = 40
-2(40) + -10 = -3

Multiply -2 * 40
-80 + -10 = -3

Combine like terms: -80 + -10 = -90
-90 = -3

Solving
-90 = -3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 31=5x+1 | | x^2+2x+3=18 | | 0.75q=24 | | P=1+0.03x | | 9x+4=9(x+4) | | X-20=X | | 2a-3a=7 | | 13x=46 | | 0.25x-0.4=1.6 | | D=40-15x | | 2x+8x+15=0 | | 5X-5-40=4X-16 | | 3(2x-1)+3=2(x-5) | | 2x^4-2x^3+4x^2+3x-7=02 | | 3(4y-9)=12 | | 12(x-1)=6x+36 | | x^5+x^4-2x^3+4x^2+3x-7=0 | | x^500+7=0 | | x/18+=-2 | | 5-2x-8x-7=8-8x | | 5x-3y= 56 | | 4x-24=-2x+6 | | C+9=2c+5 | | y-7=3(x-4) | | 4y=-9x+10 | | 4+6s-1=7s+15-5s | | (2x-1)=x+3 | | 3x+5x-2p+4p= | | 10y+5x=25 | | -11+3x+4=17 | | -7x-8y=12 | | 0=-4 |

Equations solver categories